Immunocytotoxic Effect of Aqueous Leaf Extract of Cassia occidentalis on Human Peripheral Blood Mononuclear Cells and Neutrophils - Hamid, K. M.; Yakubu, A.,; Sani, S. A.,; Kalgo, M. U; Isiyaku, A.; Umahi, N. P. F.,; Garba, Y. B.,; Aliyu, M.; Isah, S. Y.; Abubakar, U. (UMYU Journal of Microbiology Research)
The study evaluates the potential immunocytotoxic effect of aqueous leaf extract of Cassia occidentalis on human peripheral blood mononuclear cells (PBMCs) and Neutrophils. Different concentrations (25 µg/ml, 50 µg/ml, 100 µg/ml) of the extract were prepared.  Six millilitres (6ml) of peripheral blood from consented healthy volunteers was collected and PBMCs and neutrophils were isolated on Histopaque media. The viability of PBMCs and neutrophils was determined using trypan blue dye exclusion methods. One-way analysis of variance was used in analysing the results. Total viable cell count (TVCC) for PBMCs and neutrophils yielded 298.9 x 104 cells/ml and 327.9 x 104 cells/ml respectively. The TVCC of the highest concentration (100 µg/ml) of the extract used for the treatment of PBMCs was 192.7 x104 cells/ml and that of neutrophil was 50.47 x104 cells/ml equivalent to 82.51% and 61.71% mean viability percentages respectively. The PBMCs and neutrophils treated with 25 µg /ml of the extract have the highest mean percentage viability scores of 94.88% and 74.61% respectively. There was a significant difference in the mean percentage viability when control PBMCs was compared with those treated with 100 µg/ml (p<0.0001) and also when control neutrophils was compared with those treated with 25 µg /ml (p=0 .02), 50 µg /ml and 100 µg /ml (p<0.0001) respectively. The cell viability tends to decrease in a dose-dependent manner. The aqueous leaf extract of C. occidentalis has a potent cytotoxic effect on both cells, especially at a higher dose. The study recommends an in-depth study to improve the credence of the present study findings.